Analysis of Creative Thinking Ability in Solving Problems Based on Students' Learning Styles - Medyasari, Larasati Tiara; Zaenuri, Zaenuri; Dewi, Nuriana Rachmani; Wijayanti, Kristina (Universitas Muhammadiyah Mataram, 2026)
Mathematical creative thinking ability plays a crucial role in helping students solve everyday problems. This study aimed to assess students' creative thinking abilities by categorizing them into auditory, visual, and kinesthetic learning styles based on various indicators of mathematical creative thinking ability. This study aims to assess students' creative thinking abilities by categorizing them into auditory, visual, and kinesthetic learning styles based on four indicators of mathematical creative thinking abilities, namely fluency, flexibility, novelty, and elaboration. This research is a qualitative descriptive study. The data collection methods used in this study include tests to determine students’ mathematical creative thinking abilities, interviews, and documentation. The research findings were analyzed and classified into categories representing visual, auditory, and kinesthetic learning styles, with one research subject selected from each category out of 31 students. The results of the research are students with a visual learning style could solve problems fluently and efficiently while drawing accurate conclusions. Additionally, visual learners could approach problems in multiple ways and solve them independently with innovative thinking. Students with an auditory learning style could interpret problems but required more communication skills to effectively convey their ideas, draw appropriate conclusions, or evaluate the problems encountered. Lastly, students with a kinesthetic learning style required additional assistance in solving problems and responding to the given indicators.